CLL: novel prognostics, and updates on therapy 2 - Brown, Jennifer R. (Henry Stewart Talks, 2015)
Relapsed therapy in CLL, Targeted therapy, BTK inhibition, PI3K delta inhibition, Clinical trials (initial vs. relapsed)